WORKSHOP DAN PENDAMPINGAN PTK KOLABORATIF DI SD N TAMANSARI 1 DAN 2 YOGYAKARTA - Warniasih, Kristina; Rahmawati, Selly; Utami, Niken Wahyu (Universitas PGRI Yogyakarta, 2019)
The problem experienced by service partners is the lack of knowledge of teachers related to CAR (Class Action Research) and its implementation so that teachers at Tamansari 1 and 2 Elementary Schools do not carry out CAR. In addition, the existing CAR trainings are not carried out continuously so that they do not bring results and motivate teachers to do CAR. The purpose of this community service is to strengthen CAR material to improve CAR-related knowledge, namely the basic concept of CAR, problem identification and problem solving in CAR, development of CAR Instruments, preparation of CAR proposals, CAR implementation and writing of CAR reports. In addition, the purpose of this PKM is to provide assistance in the preparation and implementation of CAR by guiding CAR 1 and 2 Yogyakarta elementary school teachers.The method used in the implementation of this service was the Workshop carried out with the lecture method (face to face), demonstration (practice), and the distribution of modules for strengthening CAR material and assistance was carried out with the method of coaching and implementing CAR together.community service results are that teachers in SDN Tamansari 1 and 2 can better understand the importance of CAR concepts, implementation of CAR, and CAR reporting.Keywords: Workshop, CAR, Collaborative.